Shariah Requirements versus Contemporary Economics Realities: Influx of Muslim Beggars in Sabon-Zongo Accra - Kuyateh, Mustapha Abdullah (Ijtimā iyya Journal of Muslim Society Research, 2023)
This study explores the phenomenon of begging with a particular focus on Shariah Requirements Versus Contemporary Economics Realities: Influx of Muslim Beggars in Sabon-Zongo Accra. Overall, the study contributes towards filling the enormous gap in the literature on begging in Muslim communities in Ghana and adds other dimensions to the phenomenon of both child and adult begging in general demonstrating the complexity and different facades of the phenomenon. The methodology employed was qualitative, whilst structured interview as a method was used in gathering the necessary information needed for this article. In discussing the findings, the article analyses how this practice works and seeks to gain insight into the interrelationships of the children with their adult partners both at the family levels and at the street level as well as the implications of these interrelationships on the level of agency and vulnerability of the children involved. More importantly, the article highlights the experiences and voices of beggars by looking at the economic realities and the role Islam plays alleviating the plights of beggars. It also highlights the processes that lead to the manifestation of the phenomenon as we see it; that is, why are children used as partners and not adults, and how that is influenced and shaped by power relations and the society’s understanding of what is right and wrong for the child.